NILAI-NILAI PROFETIK DALAM PENGEMBANGAN LASIZAWA DESA PONGGOK - Muhammad Fikri Mubarok; Firda Imah Suryani (Academica: Journal of Multidisciplinary Studies, 2020)
This paper objectives to understand prophetic values have accepted from Prophetic Social Sciences (ISP) in LasiZawa’s Development Strategy. The Prophetic Values have accept to be research variabel because the significancy of basic LasiZawa Development so close with religious life that make dialectic for village society. This research used qualitative approach, the research methode using case studies. The collect data methode with in depth interview with LasiZawa’s Commitee, Village Chairman and observation. This paper conclude that there is a dialectic of social reality that is not ideal in transformation of Ponggok Tourism Village. The establisment of LasiZawa which is a response to this social reality. The newness of this tesearch lies in the institutionalization of ZISWAF institution by village government and managed independently and upholding prophetic values.Keywords: Prophetic Value; LasiZawa; Ponggok Village